APLIKASI LOCATION BASED SERVICE AGEN TRAVEL DI KOTA SEMARANG (Information Technology and Telematics, 2015)
Abstraksi The development of transportation is growing rapidly which makes a lot of people competing to run a transportation business . Travel is one of transportation that much in demand by the users because it can provide comfort zone to the passengers as well as to minimize the occurrence of crime in it. The enthuses travel grew a travel agents that spread in the city of Semarang. To facilitate the user in searching for existing travel agents in the city of Semarang, he built the travel agent site search applications to allow users to search. Subjects of this study is to make an application Location Based Service (LBS). In the development of this application using Eclipse Luna and Google API. While searching the user's position utilizing Global Positioning System (GPS) and Driving Route. This system is capable of displaying the path and the time required for a travel agency locations to be addressed by the user. From the applications that have made the application can provide the longest and shortest path and show the path to the destination and can provide information on the distance between the user's position with the travel agency locations in the city of Semarang based Google Directions API. Key Word: Travel Agent, Mobile, Android, GPS (Global Positioning System), Google Maps API, LBS (Location Based Service).